Degradasi Zat Warna Metil Violet Menggunakan Metoda Sonolisis Dengan Katalis ZnO-Ag - Abdul Rafi Jelani; Hary Sanjaya (Jurnal Periodic Jurusan Kimia UNP, 2022)
Methyl violet is a dye that is often used in the textile industry. Methyl violet contains aniline which is toxic, mutagenic, and carcinogenic. These compounds cause cancer and gene mutations in living tissue. In addition, methyl violet is also difficult to degrade in waste so it requires serious handling. This study aims to determine the optimum time and optimum mass of ZnO-Ag catalyst against Methyl violet degradation by the sonolysis method. The absorbance value was obtained using a UV-Vis spectrophotometer. The results stated that the Methyl violet solution had a maximum wavelength of 582 nm. The maximum time to degrade Methyl violet with ZnO catalyst was obtained at 90 minutes with %D 85.917% and the maximum mass of catalyst to degrade methyl violet with 10% ZnO-Ag catalyst was obtained at 87.97% mass.